Guide to JCT Intermediate Building Contract 2016 - Lupton, Sarah (RIBA Publications, 2017)
Guide to JCT Intermediate Building Contract 2016 is a practical guide to the operation and administration of JCTs IC16 suite of building contracts including both IC and ICD. All of the contracts provisions, procedures and conditions are organised and explained by subject, clearly distinguishing the different obligations due to various parties and the contractual issues arising during the course of a job - all backed up by the latest legislation and case law.